Contemporary prostate biopsy reporting: insights from a survey of clinicians' use of pathology data. Issue 10 (2nd May 2018) - Varma, Murali; Narahari, Krishna; Mason, Malcolm; Oxley, Jon D; Berney, Daniel M
Abstract : Aim: To determine how clinicians use data in contemporary prostate biopsy reports. Methods: A survey was circulated to members of the British Association of Urological Surgeons and the British Uro-oncology Group. Results: Responses were received from 114 respondents (88 urologists, 26 oncologists). Ninety-seven (94%) use the number of positive cores from each side and 43 (42%) use the % number of positive cores. When determining the number and percentage of positive cores, 72 (71%) would not differentiate between targeted and non-targeted samples. If multiple Gleason Scores (GS) were included in a report, 77 (78%) would use the worst GS even if present in a core with very little tumour, 12% would use the global GS and 10% the GS in the core most involved by tumour. Fifty-five (55%) either never or rarely used perineural invasion for patient management. Conclusions: The number of positive cores is an important parameter for patient management but may be difficult to determine in the laboratory due to core fragmentation so the biopsy taker must indicate the number of biopsies obtained. Multiple biopsies taken from a single site are often interpreted by clinicians as separate cores when determining the number of positive cores so pathologists should also report the number of sites positive. Clinicians have a non-uniform approach to the interpretation of multiple GS in prostate biopsy reports so we recommend that pathologists also include a single 'bottom-line' GS for each case to direct the clinician's treatment decision.